Carl Stumpf - Blaustein, Leopold (Phainomena (Ljubljana), 2025)
The text is a posthumous tribute to Carl Stumpf. The text summarizes the main points of Stumpf ’s philosophy and psychology by tracking the main phases in his philosophical development. The text introduces the notions of phenomenology and eidology.
Keywords: descriptive psychology; deskriptivna psihologija; eidologija; eidology; eksperimenti; experiments; fenomenologija; phenomenology; Stumpf